Battered women a psychosociological study of domestic violence - Roy, Maria (New York Van Nostrand Reinhold Company, 1977)
Explores the causes of domestic brutality, outlines preventive measures, and offers methods for helping victimized families.
Wifebeating : a recurring phenomenon throughout history / Terry Davidson -- A current survey of 150 cases / Maria Roy -- No place to go : the social dynamics of marital violence / Richard J. Gelles -- Wifebeating, husbandbeating-a comparison of the use of physical violence between spouses to resolve marital fights / Suzanne K. Steinmetz -- Battered women : a social psychological perspective / Suzanne Prescott & Carolyn Letko -- The neurology of explosive rage : the dyscontrol syndrome / Frank A. Elliot -- Psychological aspects of wifebattering / Natalie Shaines -- Men who assault their wives / M. Faulk -- Clinical aspects of wifebattering / John R. Lion -- Some thoughts regarding the criminal justice system and wifebeating / Maria Roy -- Legal solutions : equal protection under law / Emily J. Goodman -- International Association of Chiefs of Police training key #245 -- International Association of Chiefs of Police training key #246 -- Domestic assault : the police response / Darrel W. Stephens -- Family crisis intervention : from concept to implementation / Morton Bard -- A sociological perspective on the prevention and treatment of wifebeating / Murray A. Straus -- Mediation and the community dispute center / Fred Dellapa -- Yo yo children : a study of 23 violent matrimonial cases / NSPCCSchool of Social Work, London, England -- Battered women ; battered children / Margaret Varma -- Legislative needs and solutions / Barry Kutun -- A model for services / Maria Roy.
Includes bibliographies and index.
Keywords: Abused women; Wife abuse